2006
DOI: 10.2169/internalmedicine.45.1590
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HBs-Positive Liver Failure Due to Hepatitis B Virus Reactivation Induced by Rituximab

Abstract: A 59-year-old man developed acute hepatitis with reactivated hepatitis B virus (HBV) following administration of rituximab

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 18 publications
1
67
0
2
Order By: Relevance
“…Various studies have shown that patients with chronic HBV infection are at risk of HBV reactivation during chemotherapy 7,11,[21][22][23][24][25] and recently, the use of rituximab has also been demonstrated to increase the rates of viral infection and viral reactivation. [11][12][13][14] In contrast, the risk of developing HBV-related liver complications after chemotherapy and immunotherapy in patients with past HBV (isolated HBcAb positive) infection has not been well studied. The results of the current study found the risk of HBV reactivation during the course of systemic chemotherapy to be low; only 1 (1.5%) of the 67 patients experienced reactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that patients with chronic HBV infection are at risk of HBV reactivation during chemotherapy 7,11,[21][22][23][24][25] and recently, the use of rituximab has also been demonstrated to increase the rates of viral infection and viral reactivation. [11][12][13][14] In contrast, the risk of developing HBV-related liver complications after chemotherapy and immunotherapy in patients with past HBV (isolated HBcAb positive) infection has not been well studied. The results of the current study found the risk of HBV reactivation during the course of systemic chemotherapy to be low; only 1 (1.5%) of the 67 patients experienced reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the association between rituximab and HBV reactivation is still unknown, although a study by Sera et al has shown that rituximab suppresses the B lymphocytes, impairing the number and function of B lymphocytes, and may result in HBV reactivation. 11 Rituximab appeared to reduce the antibody to hepatitis B surface antigen (HBsAb), and thus might induce an immunological environment that allows for easy HBV reactivation. 12 Several case reports suggest that rituximab in combination with chemotherapy may increase the risk of HBV reactivation.…”
mentioning
confidence: 99%
“…In the same cohort of patients the incidence of HBV reactivation rose significantly in the past decade, after the introduction of rituximab, a monoclonal antibody targeted against the CD20(+) lymphocytes (2,3). In this setting, reactivation was recorded even in HBsAb (+) patients (4). In patients with rheumatic diseases, analogous cases are still mainly anecdotal.…”
mentioning
confidence: 99%
“…The majority of the liver derangements induced by cryoablation and sorafenib were transient and improved after stopping sorafenib. Furthermore, there are recent reports regarding the reactivation of hepatitis B infection in chronic hepatitis B carriers who received targeted therapy alone for the treatment of underlying malignancy [24,25] . Thus, it is possible that the administration of sorafenib will likewise lead to the reactivation of the underlying hepatitis B infection and result in worsening liver function, because most patients with advanced HCC in Asia are chronic hepatitis B carriers.…”
Section: Discussionmentioning
confidence: 99%